1999
DOI: 10.1590/s1679-87591999000100002
|View full text |Cite
|
Sign up to set email alerts
|

Environmental forcing on phytoplankton biomass and primary productivity of the coastal ecosystem in Ubatuba region, southern Brazil

Abstract: A time series of chlorophyll a and in situ primary production sampled over a period of 33 days during summer in Ubatuba region, southeastem Brazil, was subjected to multivariate and harmonic analysis. Principal Component Analysis has revealed four factors interpreted as (i) South Atlantic Central Water forcing; (ii) Transient ftontal systems and rain fali forcings; (iii) Wind forcing normal to the coast; (iv) Wind forcing parallel to the coast, as main factors in the variability of the phytoplankton biomass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0
39

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(76 citation statements)
references
References 25 publications
5
30
0
39
Order By: Relevance
“…The coastal water (CW) in Ubatuba has a salinity of 32-33 and temperatures of ≥25°C (Castro-Filho et al 1987). Given the presence of only small-sized rivers in the enclosed bays, minimal riverine input accounts for the meso-oligotrophic characteristics of the CW (Castro & Miranda 1998;Gaeta et al 1999). Nutrient concentrations (e.g.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The coastal water (CW) in Ubatuba has a salinity of 32-33 and temperatures of ≥25°C (Castro-Filho et al 1987). Given the presence of only small-sized rivers in the enclosed bays, minimal riverine input accounts for the meso-oligotrophic characteristics of the CW (Castro & Miranda 1998;Gaeta et al 1999). Nutrient concentrations (e.g.…”
Section: Study Areamentioning
confidence: 99%
“…nitrate, phosphate) are low during most of the year and the phytoplankton community is dominated by nanoplanktonic species (Aidar et al 1993;Gaeta et al 1999). In spring and summer, however, upwelling of cold and nutrient-rich water (South Atlantic Central Water, SACW: salinity ≤36.4 and temperature ≤20°C) to the euphotic zone and higher rainfall can drive sporadic blooms of opportunistic diatoms (Castro-Filho et al 1987;Aidar et al 1993;Gaeta et al 1999). Short-term sediment resuspension events, which are frequent during passage of cold fronts (i.e.…”
Section: Study Areamentioning
confidence: 99%
“…The study site, located in Ubatuba, a city located at the tropical ⁄ subtropical boundary of SE Brazil, is characterized by the presence of small bays and is exposed to river run-off (Mahiques et al 1998) and slight variations in water temperature. Sporadic increases in new production are driven by the higher rainfall during summer and by the presence of the cold and nutrient-rich South Atlantic Central Water (SACW) in the inner shelf (>20 m depth) (Castro Filho et al 1987;Aidar et al 1993;Gaeta et al 1995Gaeta et al , 1999. Blooms of opportunistic diatoms can be observed during SACW advection in the euphotic zone.…”
Section: Study Areamentioning
confidence: 99%
“…Blooms of opportunistic diatoms can be observed during SACW advection in the euphotic zone. However, nanoflagellates dominate the phytoplanktonic community for most of the year, when the low salinity Coastal Water mass is present (Gaeta et al 1995(Gaeta et al , 1999Yoshinaga et al 2008). Lipid biomarkers extracted from the sediments revealed that phytoplankton-derived material constitutes the main source of organic carbon in the sediments of Ubatuba, whereas terrestrial material derived from continental run-off accounts for a small contribution to the total organic carbon pool, even during summer, when the precipitation is higher (Yoshinaga et al 2008).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation